Magnetic resonance angiography (MRA) in preoperative planning for patients with 22q11.2 deletion syndrome undergoing craniofacial and otorhinolaryngologic procedures. (November 2020) - Kimia, Rotem; Elden, Lisa; Dailey, Julia; Kodavatiganti, Mallika; Crowley, T. Blaine; McGinn, Daniel E.; Bailey, Alice; Zackai, Elaine H.; McDonald-McGinn, Donna M.; Jackson, Oksana A.
Abstract: Introduction: Patients with 22q11.2 deletion syndrome (22q11.2DS) have a variety of anatomic anomalies. For surgeons operating in proximity to the retropharynx, the most pertinent is medial displacement of the internal carotid arteries. The purpose of this study is to describe the preoperative use of magnetic resonance angiography (MRA) in surgical planning and update the incidence rate of medial carotid displacement in patients with 22q11.2DS. Methods: This is a retrospective cohort study of patients with a confirmed diagnosis of 22q11.2 deletion and preoperative MRA <18 years old who underwent tonsillectomy, adenoidectomy, Furlow palatoplasty (FPP), posterior pharyngeal flap (PPF), sphincter pharyngoplasty (SPP), or submucosal cleft palate (SMCP) repair between January 1st, 2008 and December 31st, 2019. Results: Ninety patients who met the inclusion criteria underwent 133 procedures. The majority identified as Caucasian (84.4%); 52.2% were female. Cervical MRA was more likely to be ordered before a PPF (80.9%) and tonsillectomy (72.7%) over a FPP (47.6%) or adenoidectomy (11.1%). Carotid medialization was visualized in 23 patients (25.6%) and was mild in 11 cases, moderate in 7 cases, and significant in 5 cases. There was no association between sex, race/ethnicity, or genetic diagnosis with carotid medialization. Flap shortening was necessary in 20% of PPF cases to avoid injuring the medialized vessel. Conclusion: Patients with 22q11.2DS may have higher rates of medialization of the carotid arteries than previously thought. Given the risk for complications in these patients during pharyngeal operations, there may be a critical place for MRA in surgical planning for patients with 22q11.2DS.